Scientific methodical work in the histiry of native and foreign higher education (the second half of the16th- the beginning of the 20th century) - Степанець, І. О. (Scientific notes of the pedagogical department, 2018)
The tasks of the current scientific methodic work in the system of educational establishments are updated. The attempt of  retrospective review of the main achievements of philosophers, thinkers, pedagogues, scientists as to the development of scientific methodical supplying of educational process, the creation of scientific methodical complexes of higher educational establishments in the indicated limits(the second half of 16th –the beginning 0f 20th ) was realized.The article is devoted to the historical pedagogical analysis of the origin of scientific methodical work in the native and foreign pedagogical conceptions and practice of the higher establishments. Based on the analysis of works and ideas and on the pedagogical practice, the peculiarities of the development of scientific methodical work with the help of characterizing its aims, contents, forms and place in the structure of higher educational establishments were examined.The conclusions as to the stages of development and functions of scientific methodical complexes at universities and their structural subdivisions that give opportunities to indicate tendencies of their development at the mentioned and other periods are made in the article.